ADCP current measurements (38 and 75 kHz) during MARIA S. MERIAN cruise MSM61 - Fiedler, Björn; Karstensen, Johannes; Czeschel, Rena; Krahmann, Gerd (PANGAEA, 2021)
Two Teledyne RDI Ocean Surveyor systems with 38 and 75 kHz transmission frequency were used. Data was processed with a software package developed at GEOMAR following the GO-SHIP standards (Firing and Hummon, 2010). The data was subsequently averaged over one minute intervals, converted to a NetCDF based format.